ROMANTISME DALAM ANTOLOGI PUISI KIDUNG LELUHUR CIANJUR KARYA YUSUF GIGAN (ROMANTISM IN THE ANTHOLOGY OF KIDUNG LELUHUR CIANJUR BY YUSUF GIGAN) - Mia Fatimatul Munsi (Universitas Lambung Mangkurat, 2022)
Romantism In The Anthology Of Kidung Leluhur Cianjur By Yusuf Gigan. The anthology of the poem Kidung Ancestor Cianjur by Yusuf Gigan tells a lot about important and historical places, mentioning the names of historical figures in Cianjur, as well as expressing ideas and views on life. Therefore, this study aims to describe romanticism in the anthology of poetry Kidung Leluhur Cianjur by Yusuf Gigan. The method used is descriptive method. Data were collected by using documentary study techniques and content analysis. Furthermore, the data analyzed were 50 poems contained in the poetry anthology Kidung Leluhur Cianjur by Yusuf Gigan. The results of data analysis concluded that the poetry anthology book Kidung ancestral Cianjur by Yusuf Gigan contains romanticism, namely many expressions of the poet about his longing for Cianjur historical figures, God, closest people, historical places, nature (rice fields, fields, rivers, parks, mountains, and the city of Cianjur as his hometown). In addition, it also looks a view of life or ideals.Keywords: romanticism, poetry, anthology, local wisdom, kidung leluhur cianjur.Romantisme dalam Antologi Puisi Kidung Leluhur Cianjur karya Yusuf Gigan. Antologi puisi Kidung Leluhur Cianjur karya Yusuf Gigan banyak menceritakan tempat penting dan bersejarah, penyebutan nama tokoh bersejarah Cianjur, juga pengungkapan ide dan pandangan hidup. Oleh karena itu, penelitian ini bertujuan untuk mendeskripsikan romantisme dalam antologi puisi Kidung Leluhur Cianjur karya Yusuf Gigan. Adapun metode yang digunakan adalah metode deskriptif. Data dikumpulkan dengan teknik studi dokumenter dan analisis isi. Selanjutnya, data yang dianalisis berjumlah 50 puisi yang terdapat dalam antologi puisi Kidung Leluhur Cianjur karya Yusuf Gigan. Hasil analisis data diperoleh kesimpulan bahwa buku antologi puisi Kidung leluhur Cianjur karya Yusuf Gigan mengandung romantisme yaitu banyak ungkapan penyair tentang kerinduannya terhadap tokoh bersejarah Cianjur, Tuhan, orang terdekat, tempat bersejarah, alam (sawah, ladang, sungai, taman, gunung, dan kota Cianjur sebagai kampung halamannya). Selain itu juga tampak pandangan hidup atau cita-cita.Kata-kata Kunci: romantisme, antologi, puisi, kearifan lokal, kidung leluhur cianjur.